If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(2x+19)+(2x+23)=10
We move all terms to the left:
(2x+19)+(2x+23)-(10)=0
We get rid of parentheses
2x+2x+19+23-10=0
We add all the numbers together, and all the variables
4x+32=0
We move all terms containing x to the left, all other terms to the right
4x=-32
x=-32/4
x=-8
| 13(6m+21)=m-7 | | 2x+3÷5=3 | | 6x+7x=132 | | 7x-14=5(x+2) | | n+4/5=5 | | (2x-11)+(2x-4)=13 | | 3(2x–7)=5x–x–11 | | 9a+3;9=5 | | 21(c-1)-19(c+1)=2(c-20) | | 5x+2°=9x-10° | | 7m+4=2(m-1)+7 | | 9m-5=-32 | | 0.25x+11=3 | | (2x—11)+(2x-4)=13 | | 7+.14x=12+.10x | | 3(n‐5)=-21 | | 4(x-6)=6x+12 | | 3x+3=15+5 | | 197-4.2x=218-7.7x | | p-1/5=9 | | 3x-1=-35 | | -8(7m+4)=-6(8m+9) | | 2w+10–8w=-38 | | 44000+3300x=52000+2300x | | 82=1-9x | | 2∣x−4∣+3=4 | | 17y-3(4-2y)=11(y-1)+12y-1 | | (s-4)2–81=0 | | 3. (s-4)2–81=0 | | 20+5x=9x+6 | | 6x-82=-3x+80 | | -6x+14=-34 |